Application of Biofilter System for Domestic Wastewater Treatment - Noor Suraya, Romali; Nadiah, Mokhtar (Penerbit UMP, 2011)
Nowadays, clean water resources are reduced due to water pollution problems. Pollution carried by the domestic wastewater is considered as one of the contributors to water pollution problems. One of the ways to treat wastewater is by constructing a biofilter system at the point sources to treat the polluted water before being discharged into rivers. This study emphasizes on the utilization of a filtering system using natural occurring materials such as empty fruit bunch (EFB) from oil palm fibre, mudball from effective microorganism (EM), activated carbon from coconut shell, charcoal, sand, and gravel as the filtering materials. Experiment was conducted at Universiti Malaysia Pahang (UMP), where a site scale filtering system was set up to observe the potential of the system in removing pollutants. The results were analyzed by evaluating the water quality parameters such as pH, SS, BOD, COD, and AN in term of their percentages of removal and comparison to Standard A and Standard B of Environmental Quality Act (1974). For overall, the biofilter system was found to be capable in removing pollutants in domestic wastewater where the maximum percentages of removal for parameters SS, COD, BOD, and AN are as high as 83.08%, 51.60%, 72.42%, and 85.71% respectively. The study also indicated that the performance of the biofilter system in improving parameters SS, COD, BOD, and AN increased as the quantity of filtering materials applied increased.